Variants in the SNCA Locus Are Associated With the Progression of Parkinson's Disease - Luo, Ningdi; Li, Yuanyuan; Niu, Mengyue; Zhou, Liche; Yao, Mengsha; Zhu, Lin; Ye, Guanyu; Kang, Wenyan; Liu, Jun (Frontiers in Aging Neuroscience, 2019)
Background: Genetic factors have a well-known influence on Parkinson's disease (PD) susceptibility; however, no previous studies have investigated the influence of SNCA mutations on the natural history of PD using a prospective follow-up study. The aim of this study was to assess the risk factors of variation of SNCA on the prognosis symptoms of PD patients. Methods: Fifty PD patients were recruited with 38 v-PSG confirmed PD+RBD patients, and the median follow-up period was 30 months. All patients underwent a comprehensive clinical evaluation at baseline and follow-up, and six SNPs of SNCA (rs356165, rs3857053, rs1045722, rs894278, rs356186, and rs356219) were analyzed. Cox proportional hazards regression models and Kaplan–Meier plot analysis were used to assess the associations between the SNCA variation and the primary and secondary progression outcomes. Results: Based on the clinical assessment, we found that hyposmia was substantially easier to aggravate. Regression analysis showed that patients with the T allele of rs1045722 and the G allele of rs356219 presented a 34 and 20% decreased risk of progression to the H-Y stage, respectively (p = 0.022; p = 0.005). While for rs894278, G allele patients showed a 47% decreased risk of olfactory dysfunction (p = 0.029). Further subgroup analysis showed that PD+RBD patients with rs356219/G exhibited a 30% and 20% decreased risk of progression on the H-Y stage and MoCA score (p = 0.038; p = 0.045). Conclusions: Our results indicated that genetic variation in SNCA may contribute to variability natural progression of PD and could possibly be used as a prognostic marker.